DFSMSrmm primer - Lovelace, Mary (IBM redbooks., 2005)
DFSMSrmm from IBM is the full function tape management system available in OS/390 and z/OS. With DFSMSrmm, you can manage all types of tape media at the shelf, volume, and data set level, simplifying the tasks of your tape librarian. Are you a new DFSMSrmm user? Then this IBM Redbooks publication introduces you to the DFSMSrmm basic concepts and functions. You learn how to manage your tape environment by implementing the DFSMSrmm management policies. Are you already using DFSMSrmm? In that case, this book provides the most up-to-date information about the new functions and enhancements introduced with the latest release of DFSMSrmm. You will find useful information for implementing these new functions and getting more benefits from DFSMSrmm. Do you want to test DFSMSrmm functions? If you are using another tape management system and are thinking about converting to DFSMSrmm, you may start DFSMSrmm and run it in parallel to your current system for testing purposes. This book is intended to be a starting point for new professionals and a handbook for using the basic DFSMSrmm functions. Please note that the additional material referenced in the text is not available from IBM.